Mercury Behaviorin Saline Soil Containing Humic Acidand Zeolite - al., Alaa E. Alsaleh et (International Journal of Advanced Science and Technology, 2019)
Humic acid (HA) and zeolite (Zol) can reduce or even suppress mercury (Hg) mobility and bioavailability in soil. This experiment performed as a completely randomized design with three replications. For this purpose, 6 kg of saline soil in columns was treated with HA and Zol both at concentrations of 0 and 0.5 mg kg. They were also irrigated with three mercury levels of 0, 75, and 150 mg /l using HgCl2 salt. Irrigation with mercuric chloride was done every five days with equal amounts of prepared solution to each column. After 20 days, the leachate was collected from each column and mercury concentration was determined in the leachate. Then, the total and available mercury were determined in 5 sections of soil with 10 cm thickness. The resultsindicated that HA and Zol treatments play an important role in controlling Hg in saline soil. Further, HA and Zol increased the retention of total Hg in saline soil. Accordingly, HA and Zol reduced the amount of available Hg in soil and prevented transportation and leaching of Hg from the saline soil, thereby lowering the mercury content in the leachate. Note that the positive impact of HA was greater than that ofZol. Keywords: Mercury toxicity, organic, inorganic,treatments, saline soil.